Pengaruh Wisata Religi Sunan Giri dalam Meningkatkan Pendapatan dan Kemajuan Ekonomi Masyarakat Gresik - Muhammad Thoriq Farchan (AL-UJRAH, 2025)
Sunan Giri religious tourism in Gresik district has a significant influence on the income and economic progress of the Gresik community. This study presents an explanation of the influence of religious tourism Sunan Giri in Gresik district in increasing the income and economic progress of the Gresik people. This research aims to provide information and insight for readers, especially the local government, because the location of the two great ulama's graves is very strategic and also has a big impact on the people of Gresik, especially in the economic field. This phenomenon was studied using a qualitative method with descriptive presentation which was analyzed based on form of literature studies with a research focus on economic actors around the Sunan Giri tomb and the Gresik district government in developing and utilizing the religious tourism sector to maximize the economy in Gresik Regency. This study found that by developing and utilizing Sunan Giri religious tourism, it will increase income and progress in the economic sector, especially the Sunan Giri tomb in the Kebomas sub-district, as well as economic centers that utilize religious tourism.